Schwannoma of the Median Nerve at the Wrist and Palmar Regions of the Hand: A Rare Case Report - Harun Kütahya; Ali Güleç; Yunus Güzel; Burkay Kacira; Serdar Toker (Case Reports in Orthopedics)
Schwannomas are also known as neurolemmas that are usually originated from Schwann cells located in the peripheric nerve sheaths. They are the most common tumours of the hand (0.8–2%). They usually present solitary swelling along the course of the nerve however multiple lesions may be present in cases of NF type 1, familial neurofibromatosis, and sporadic schwannomatosis. Schwannomas are generally represented as an asymptomatic mass; however pain, numbness and fatigue may take place with the increasing size of the tumour. EMG (electromyelography), MRI (magnetic resonance imagination), and USG (ultrasound) are helpful in the diagnosis. Surgical removal is usually curative. In this paper, we present a 24-year-old male referred to our clinic for a lump located at the volar side of the left wrist and a lump located in his left palm and numbness at his 3rd and 4th fingers. Total excision was performed for both lesions. Histopathological examination of the masses revealed typical features of schwannoma. At the 6th-month followup the patient was symptom-free except for slight paresthesia of the 3rd and the 4th fingers. For our knowledge, this is the second case in the literature presenting wrist and palm involvement of the median nerve schwannoma.